Assessment of Safety Measures and Operational Challenges of Inland Waterway Transport along Oron - Calabar Route, Nigeria - Okon*, Idongesit Edem; Jatau, Solomon Usman; Attah, Anthony Abutu (Aceh International Journal of Science and Technology, 2023)
This study assessed the safety measures and operational challenges of inland waterway transport along the Oron - Calabar route. Observation and structured questionnaires were used for the collection of data. Quantitative data was analyzed using descriptive statistics, while qualitative data was coded and analyzed using the 4-point Likert scale, which was converted to a relative importance index (R.I.I.) for each factor, posing a challenge to operators. The result showed that safety equipment was provided onboard boats by operators. The R.I.I. computed showed that boat and engine replacement (R.I.I. = 0.874) was the most challenging factor, while water hyacinth (R.I.I. = 0.418) was the least. Other challenges were frequent bad weather conditions, high running costs, floating logs and debris, extortion by law enforcement agents, difficulty making headway against the opposite current, high cost of safety equipment, passengers' refusal to adhere to safety measures, and poor berthing facilities in their order of impact. Proper funding and enforcement of safety measures are hereby recommended.